Discussion of “Biomedical Infor -matics: We Are What We Publish” - Geissbuhler, A.; Hammond, W. E.; Hasman, A.; Hussein, R.; Koppel, R.; Kulikowski, C. A.; Maojo, V.; Martin-Sanchez, F.; Moorman, P. W.; Moura, L. A.; de Quirós, F. G. B.; Schuemie, M. J.; Smith, B.; Talmon, J. (Methods of Information in Medicine, 2013)
This article is part of a For-Discussion-Section of Methods of Information in Medicine about the paper "Biomedical Informatics: We Are What We Publish", written by Peter L. Elkin, Steven H. Brown, and Graham Wright. It is introduced by an editorial. This article contains the combined commenta -ries invited to independently comment on the Elkin et al. paper. In subsequent issues the discussion can continue through letters to the editor.
Keywords: Biomedical informatics; natural language processing; Medline; ontology